A FLUOROMETRIC METHOD IMAGING CYCLIC GMP PRODUCTION IN CEREBELLAR PURKINJE CELLS - Okada, D.; Hartell, N.A. (Japanese Journal of Pharmacology, 1997)
Due to the diffusible and labile nature of NO, identification of cells producing cGMP in response to NO has been a subject of investigation. However, earlier studies with static methods such as immunohistochemistry failed to detect cGMP production in cerebellar Purkinje cells where soluble guanylyl cyclase (sGC), the major cGMP-producing enzyme, is localized, thereby casting doubts on functions of NO and cGMP in Purkinje cells. We have introduced a novel, realtime imaging technique that allows cGMP production to be assessed in living neurons. Activity of endogenous cGMP-activating phosphodiesterase, as the cGMP detector, was monitored by reduction in the fluorescence upon hydrolysis of 2-O-anthraniloyl cGMP (Ant-cGMP). Confocal and video-based imaging techniques revealed that applications of NO donors induced rapid accelerations of Ant-cGMP hydrolysis in Purkinje cells of both in slice and culture, in a manner dependent on sGC activity. Thus, the novel method developed in the present study shows NO-dependent cGMP production in Purkinje cells for the first time, supporting a role for cGMP as a mediator within Purkinje cells in induction mechanisms underlying long-term depression. Present addresses.